The Intertextuality of Time and Space in Cross-Media Creation of “Love Recipe” - Vongpattaranon, Nilobon (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
This qualitative research is aimed to explore the intertextuality of time, space and meaning between a Thai television drama and musical theater cross-media creation called “Soot Saneha” (Love Recipe). Ethnography method is applied to this research. The results of this research revealed that the intertextuality of time consisted of set time, event time and symbolic time. The construction of time and space in musical play was adapted from television editing code, consequently, six following techniques were integrated 1) Split Screen 2) Flash Back 3) Inner Extension 4) Re-entry 5) Multiple Entrance 6) Ensemble. Lastly, the intertextual-Meaning of food is translated through the songs in musical play.